Immigration and wages: new evidence from the African American Great Migration - John Gardner (IZA Journal of Migration, 2016)
During the African American Great Migration, millions of blacks left the Southern USA in favor of cities in the North. Despite the social and economic consequences of this migration, the question of its impacts on labor markets in the North has largely been overlooked in the literature. In this paper, I use both local wage comparisons and structural simulations of the aggregate Northern labor market to provide new evidence on the effects of the Great Migration on wages in the North, redoubling the evidence that it caused large declines in wages for blacks, with little effect for whites. The agreement between my local and aggregate wage effect estimates has implications for our general understanding of how immigration and wages are related and how that relationship can be measured.
Keywords: J15; J61; R23; N32; N92; 330; Migration; Immigration; Internal migration; Great Migration; Local labor markets; National labor market; Wages; Spatial arbitrage